Effects of Simplified Ancillary Representations and Cues on Learning from Animation - Putri, D.; Boucheix, J.; Lowe, Richard (Universite Pierre-Mendes-France, 2012)
Effects of novel presentation formats on learning from animation were tested in 2 experiments. Experiment 1 recruited Johnson Laird’s notions about simplification in mental model building and compared sequential combinations of different formats (static and animated) versus repeated presentation of single formats. Comprehension measures indicated that despite participant’s mental model quality being significantly higher for the static-animated sequence, mental model scores were relatively low. Experiment 2 aimed to raise mental model quality by adding a new form of entity cueing in which functionally important aspects were cued via coloured tokens. Although eye movement data indicated the cues were effective in directing learners’ attention they did not result in further improvements in mental model quality.